A study of nutritional status of adolescent girls residing in urban slums of Guwahati city, Assam, India - Deka, Chandana; Baishya, Achyut C.; Ojah, Jutika; Barua, Kabita (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescent girl’s health covers morbidity, mortality, nutritional status and reproductive health and linked to these are environmental degradations, violence and occupational hazards. Adolescent girl’s health also has an intergenerational effect. With the aim to assess their nutritional status, a cross sectional study was carried out among adolescent girls of 10-19 years residing in the urban slums of Guwahati city.. Methods: 400 adolescent girls were interviewed from 10 randomly selected slums over a period of one year. Predesigned pretested semi structured interview schedule was used to collect socio demographic and individual information of the respondents. Hemoglobin estimation was done using colour scale method. Results: Out of 400 respondents, 34.75% were found to have a BMI lying between 15th -50th percentiles of reference value. 20.00% were found to be below 5th percentile. 33.50% of the total respondents belonged to class IV socioeconomic status, out of which 47.00% is found to have a BMI of less than 5th percentile. The study shows the prevalence of mild anaemia to be 28.46%, moderate anaemia to be 57.31% and severe anaemia 14.23% respectively. The mean haemoglobin of menstruating girls (8.87 gm%) was found to be less than in the non-menstruating girls (10.15 gm%). There was a positive association between prevalence of anaemia among the adolescent girls and worm infestation. Conclusions: Socioeconomic status is seen to have an appreciable impact in the health and nutritional status of the slum dwelling adolescent girls.